The Influence of Brand Ambassador, Product Quality, and Price on Product Purchasing Decision Store in Sidoarjo - Elsa Firdausi Nuzula; Misti Hariasih (Publikasi Indonesia, 2024)
The cosmetics industry in Indonesia is experiencing rapid growth with cosmetic products becoming part of fashion trends. This study aims to analyze the influence of Brand Ambassadors, product quality, and price on the purchase decision of Radiance Up Y.O.U Beauty serum products in Sidoarjo. This study uses a quantitative approach with survey methods and regression analysis to see the influence of these three variables on purchase decisions. The results of the study show that Brand Ambassador, product quality, and price have a significant influence on purchasing decisions. Among the three variables, price proved to be the most dominant factor influencing consumer decisions, followed by product quality and Brand Ambassador. Based on these findings, companies are advised to consider a more optimal strategy in selecting Brand Ambassadors, maintaining product quality, and setting competitive prices to attract more consumers.